Novice Nurses' Experiences With Palliative and End-of-Life Communication. (July 2015) - Hendricks-Ferguson, Verna L.; Sawin, Kathleen J.; Montgomery, Kitty; Dupree, Claretta; Phillips-Salimi, Celeste R.; Carr, Barb; Haase, Joan E.
Health care providers recognize that delivery of effective communication with family members of children with life-threatening illnesses is essential to palliative and end-of-life care (PC/EOL). Parents value the presence of nurses during PC/EOL of their dying child. It is vital that nurses, regardless of their years of work experience, are competent and feel comfortable engaging family members of dying children in PC/EOL discussions. This qualitative-descriptive study used focus groups to explore the PC/EOL communication perspectives of 14 novice pediatric oncology nurses (eg, with less than 1 year of experience). Audio-taped focus group discussions were reviewed to develop the following 6 theme categories: ( a ) Sacred Trust to Care for the Child and Family, ( b ) An Elephant in the Room, ( c ) Struggling with Emotional Unknowns, ( d ) Kaleidoscope of Death: Patterns and Complexity, ( e ) Training Wheels for Connectedness: Critical Mentors during PC/EOL of Children, and ( f ) Being Present with an Open Heart: Ways to Maintain Hope and Minimize Emotional Distress. To date, this is the first study to focus on PC/EOL communication perspectives of novice pediatric oncology nurses.